Language, Culture, and Gender: The Role of Traditional Stories in the Acceptance of Transgender Individuals - Anthony M. Mon; Elmer C. Diocares; Shella Marie I. Diocares (Future Science / FSH-PH Publications, 2026)
This qualitative study investigates the intersection of traditional storytelling, cultural heritage, and the societal acceptance of transgender individuals within the Philippine context. While historical narratives often dictate rigid gender binaries, this research explores how such stories can simultaneously act as barriers to and instruments for gender inclusivity. Through semi-structured interviews with eight transgender participants from Sta. Cruz, Zambales, the study identifies core thematic challenges, including religious discrimination, deep-seated superstitions regarding